(How) should information world maps be visually analyzed?. Issue 1 (1st February 2019) - Greyson, Devon; O'Brien, Heather; Shankar, Saguna
ABSTRACT: Information world mapping (IWM) is a participatory, arts‐based elicitation method for use in interviews about information behaviours or practices. The participant‐drawn maps that result from this technique are typically used as ancillary data sources to aid in analysis of interview transcripts; however it may be possible, and even useful, to analyze these maps as data independent of the interviews, using methods suited to image analysis. This brief paper and accompanying visual presenta‐ tion describe results of analyses of information world maps using four different and contrasting methods with accompanying examples, and issue recommendations regarding the use of qualitative content analysis, compositional analysis, conceptual analysis, and visual discourse analysis, for analysis of information world maps. These insights may be generalized to other objects (e.g., photos) created through arts‐based elicitation interviewing.